Implikasi Hukum Batalnya Perjanjian Nominee:Perbandingan Konskuensi PMH dalam Sengketa Properti Eigendom di Indonesia dan Belanda - Maukar, Michelle Regine; Huberta, Grace Amaze; Leos, Meirate; Fewsan, Kimberly; Tirta , Marcell (Syntax Corporation, 2025)
This research focuses on the comparative aspects between Indonesia and the Netherlands in facing the challenges of illegal acts committed by foreign nationals. A nominee agreement is an agreement that illegally sells or lends the identity of a local citizen, which can benefit both parties, especially foreign nationals who can purchase assets in the form of land in a country. Nominee agreements or borrowing names in property or land ownership in Indonesia are included as Unlawful Acts (PMH) under Article 1365 of the Civil Code. This is because such actions are considered legal smuggling that has the aim of avoiding or violating the Basic Agrarian Law, particularly the Principle of Nationality. If nominee agreements continue to be normalized, the economy and land in a country could be threatened by illegal ownership owned by foreign nationals. Using normative legal research methods, this research uses cross-country comparisons of regulations, rules, and how governments respond to the process of illegal identity lending.